THE USE OF AUTHENTIC TEXTS AS AN APPROACH TO DEVELOP TEACHER’S PEDA-GOGIC COMPETENCE - Hannah Hannah; Jatis Suryanto (University of Muhammadiyah Purwokerto, 2015)
The aim of this paper is particularly to provide a holistic representation of pedagogic competence related tothe use of authentic texts. Based on Undang-Undang Guru dan Dosen (UUGD) No.14, 2005, teachers are pro-fessional educators who have the main responsibilities to educate, teach, supervise, train, assess, and evaluate students. Teachers, therefore, ought to possess standard academic qualifications and a set of competence to achieve such objectives. Competence is set of a professional knowledge, skills, and behavior that must be pos-sessed, internalized, mastered, and actualized by teachers. One of those competences is pedagogic competence which focuses on the knowledge and the ability of the teacher to construct or assemble teaching resources. In relation to pedagogic competence, professional teachers should creatively adapt textbook material and other audio, visual, or mechanical aids as teaching material. Authentic texts are one of those materials that can be used by teachers to create variety. By using authentic texts teachers are enforced to create innovative teach-ing methods which also part of pedagogical skill. In other words, the use of authentic texts will also influence another ability of the teachers especially in pedagogical competence. Keywords: Pedagogic competence, authentic text, innovative teaching.